"After all, no one is superhuman here": An analysis of the perceived effects of managerial athleticism - Harri Raisio; Tero Kuorikoski; Tero Rantala; Mikko Rask (Administrative Sciences, 2021)
Executive duties have long been described as becoming more intensive and demanding. One contributing factor is a perceived increase in the complexity of the operating environment. A high level of physical fitness has been suggested to support responses to those demands. This study aims to contribute to the topic by producing a holistic view informed by asking how physically active executive-level leaders perceive the impact (whether positive or negative) of managerial athleticism on the level of the individual, organization, and society. Twenty physically active high-level leaders were interviewed for the study. The sample was almost equally split by gender, represented a diverse range of societal sectors, and engaged in many different forms of exercise. The results support previous research; however, this study provides a more nuanced view of the topic. Although the interviewees saw many good aspects of physical exercise, such as providing physical, affective, cognitive, and social resources, they were also able to think critically about their personal relationship with exercising and their attitudes toward others taking physical exercise. The study highlights the role of balancing the harmonious and obsessive aspects of the relationship with exercising. Instead of a disproportionate study of extreme cases, we conclude that it would be worthwhile studying leaders with a harmonious relationship with exercise to ensure results do not become biased and physically active leaders are not stereotyped.
Keywords: 350; organizational performance; leadership; managerial athleticism; physical fitness; well-being